Carcinogenesis in Chronic Ulcerative Colitis: Flow Cytometry - DJ Ahnen; JB McHugh; JM Bozdech; GH Warren (Canadian Journal of Gastroenterology)
Flow cytometry is a conceptually straightforward quantitative method that can be used to determine the DNA content (and many other parameters) of individual cells. It has been used in chronic ulcerative colitis to evaluate the presence of aneuploidy as a marker of colon cancer risk. In this paper, the basic principles of flow cytometry are reviewed, the current status of published studies using flow cytometric analysis of DNA content in chronic ulcerative colitis outlined, conclusions from the research are proposed and future research needs identified. Overall, aneuploidy correlates with the current best markers of cancer risk in ulcerative colitis, ie, dysplasia and established cancer. Whether aneuplo1dy will be useful for the prospective identification of individuals at increased risk for colon cancer deserves rigorous evaluation. An important technical issue of potential variability in interpretation of near diploid peaks is emphasized.